Preparation method and application of 2-amino benzothiazole loaded aminated sepiolite cross-linked self-healing antibacterial antiseptic hydrogel coating
Patent Information
- Application Number
- CN202611226860.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]然而,仅依靠水凝胶本身的物理屏障作用难以满足长期复杂环境下的防腐需求
[0021](1)防腐功能:该涂层依托PVA/OSA致密网络与HSEP-NH2构建交联结构,形成稳固物理屏障,阻挡腐蚀介质渗透,同时ABT@HSEP-NH2可缓释ABT,在金属表面形成钝化膜,从物理阻隔与活性保护两方面协同作用,大幅提升涂层长效耐腐蚀能力。
Smart Images

Figure CN123004201A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal corrosion protection and functional coating technology, specifically to a method for preparing and applying a self-healing antibacterial and anti-corrosion hydrogel coating of aminated sepiolite loaded with 2-aminobenzothiazole. Background Technology
[0002] With the rapid development of industries such as marine engineering equipment, shipping, offshore wind power, and offshore oil and gas development, the demand for metal materials to serve in complex marine environments with high salinity, high humidity, and high oxygen levels is constantly increasing. However, the presence of large amounts of chloride ions in the marine environment accelerates the electrochemical corrosion process on metal surfaces. Simultaneously, marine microorganisms easily adhere to metal surfaces and form biofilms, further inducing and exacerbating microbial corrosion, leading to a decline in the performance of metal structures, shortened service life, and even safety accidents. Therefore, developing metal protective coatings that combine high-efficiency corrosion resistance, antibacterial properties, and long-term stability has become an important research direction in the field of marine protection.
[0003] Currently, organic coatings are widely used due to their low cost, ease of application, and wide applicability. However, traditional organic coatings mainly rely on physical barriers to prevent the penetration of corrosive media. During long-term service, they are susceptible to mechanical wear, temperature changes, and environmental stress, leading to defects such as cracks, pinholes, and localized peeling. Once the coating is damaged, corrosive media can quickly penetrate to the metal substrate surface along the defects, causing localized corrosion and ultimately coating failure. Therefore, endowing coatings with self-healing capabilities and active protective functions has become an important research approach to improve their durability.
[0004] In recent years, hydrogel materials have attracted widespread attention due to their unique three-dimensional network structure, excellent flexibility, good film-forming properties, and abundant functional groups. PVA, as a commonly used hydrophilic polymer, possesses good mechanical properties, biocompatibility, and film-forming properties, and has been widely used in the construction of hydrogel coatings. OSA contains abundant aldehyde functional groups, which can undergo Schiff base reactions with amino-containing substances to form dynamic covalent bonds, thereby endowing hydrogels with excellent self-healing properties. Therefore, constructing dynamically cross-linked hydrogels based on PVA and OSA provides an important approach for developing novel protective coatings that combine structural stability and self-healing capabilities.
[0005] However, relying solely on the physical barrier function of hydrogels is insufficient to meet the corrosion protection requirements under long-term, complex environments. To further enhance the active protection capability of coatings, researchers have attempted to load corrosion inhibitors onto a carrier to achieve corrosion-triggered release. Sepiolite, a natural nanofiber silicate mineral, possesses a large specific surface area, abundant porous structure, and excellent loading capacity. Amino-modification of sepiolite not only improves its interfacial bonding with the hydrogel matrix but also enhances structural stability by forming dynamic Schiff base bonds between surface amino groups and aldehyde groups in OSA. Simultaneously, aminated sepiolite can also serve as a container-loaded active species, enabling controlled release of active species upon corrosion, thus forming an active protection mechanism.
[0006] Therefore, developing a multifunctional protective coating with PVA / OSA hydrogel as the matrix and aminated sepiolite loaded with active components as the crosslinking agent to achieve the synergistic effect of physical barrier, self-healing, active corrosion prevention and antibacterial functions is of great theoretical significance and application value for improving the long-term service reliability and safety of metallic materials in marine environments. Summary of the Invention
[0007] To solve the above technical problems, the present invention is achieved through the following technical solution: The present invention provides a method for preparing and applying a self-healing antibacterial and antiseptic hydrogel coating of aminated sepiolite loaded with 2-aminobenzothiazole. A three-dimensional hydrogel network structure is constructed using polyvinyl alcohol (PVA) and sodium alginate oxide (OSA), and ABT@HSEP-NH2 is introduced as a crosslinking agent and carrier. HSEP is surface-aminated and loaded with 2-aminobenzothiazole (ABT), which has both antiseptic and antibacterial effects, to obtain ABT@HSEP-NH2 nanocontainers. ABT@HSEP-NH2 is uniformly dispersed in the PVA / OSA hydrogel matrix and chemically bonded to the hydrogel network through dynamic Schiff base bonds formed between amino and aldehyde groups, thereby constructing a stable and dense organic-inorganic composite protective system. The PVA and OSA are compounded in a 1:1 mass ratio to form the coating matrix hydrogel.
[0008] The first aspect of this invention protects a method for preparing ABT@HSEP-NH2 nanocontainers, wherein the ABT@HSEP-NH2 is prepared using a vacuum loading method, and the prepared ABT@HSEP-NH2 has a rod-like structure. The specific preparation steps include:
[0009] Step 1: Preparation of HSEP: Grind natural sepiolite (SEP) and disperse it in deionized water. Add hydrochloric acid to adjust the pH to 4. After filtration, dry for 24 h. Add the dried SEP to distilled water and stir for 30 min. Add 30% hydrogen peroxide until no bubbles are generated. After vacuum filtration, dry for 24 h. Add the above product to 20 mL of hydrochloric acid and shake for 12 h. Filter and wash until neutral. After drying for 24 h, pulverize and pass through a 200-mesh sieve to obtain acid-treated sepiolite, denoted as HSEP.
[0010] Step 2, Preparation of HSEP-NH2: 3-aminopropyltriethoxysilane (APTES), ethanol and deionized water were sonicated until the solution was clear and transparent to obtain silane hydrolysate. Then, HSEP was added to the silane hydrolysate and sonicated for 30 min. The mixture was stirred and reacted for 12 h. After cooling, the mixture was collected by centrifugation and dried for 24 h to obtain aminated sepiolite, denoted as HSEP-NH2.
[0011] Step 3: Preparation of ABT@HSEP-NH2: Using the vacuum loading method, HSEP-NH2 was added to the ABT solution, and the mixture was stirred under vacuum and at normal pressure for 30 min each, repeated 3 times. After centrifugation and drying, ABT@HSEP-NH2 was obtained.
[0012] Furthermore, the covalent crosslinking network endows the coating with self-healing properties, and the ABT can be slowly released under external triggering, forming a protective film on the metal surface to provide active protection. The hydrogel matrix, dynamic crosslinking network and ABT slow release work together to improve the coating's self-healing, corrosion resistance and antibacterial properties.
[0013] The second aspect of this invention protects a method for preparing a PVA / OSA-based composite hydrogel coating with multiple protective functions and its application.
[0014] The specific steps for preparing the composite hydrogel coating include:
[0015] Preparation of S1 and OSA: Sodium alginate was dispersed in ethanol, and an aqueous solution containing sodium periodate was slowly added. The mixture was stirred at room temperature in the dark for 5 h. Ethylene glycol was added and stirred for 1 h to terminate the reaction. Ethanol was then added to precipitate the product. The product was filtered under vacuum and washed and purified three times to obtain a white powder. The obtained product was dissolved in deionized water and rotary evaporated for 4 h. After that, it was freeze-dried for 48 h to obtain OSA powder.
[0016] S2. Preparation of PVA / OSA hydrogel: Prepare PVA solution (95 °C, 2 h) and OSA solution (40 °C, 2 h), mix PVA and OSA solution at a mass ratio of 1:1, and denote as PVA / OSA hydrogel;
[0017] Preparation of S3, PVA / OSA / 0.25ABT@HSEP-NH2 composite hydrogel: PVA / OSA was used as the coating matrix hydrogel, and HSEP-NH2 with a content of % was added as a crosslinking agent and stirred thoroughly to obtain a composite hydrogel, which was denoted as PVA / OSA / 0.25HSEP-NH2. ABT@HSEP-NH2 was added to PVA / OSA and stirred thoroughly to obtain PVA / OSA / 0.25ABT@HSEP-NH2 hydrogel.
[0018] S4. First, clean the oxide layer, impurities, and adhering contaminants on the surface of the zinc sheet. After cleaning, dry it for later use. Let the hydrogel obtained above stand to degas. Then, use a spin coating process to evenly apply the composite hydrogel to the pretreated zinc sheet surface. After coating, place the sample in a 30 °C oven to cure for 3 h to obtain the corresponding composite hydrogel coating.
[0019] Furthermore, the spin coating process includes: firstly, forming an underlayer by spin coating at a high speed, and then continuously spin coating three layers at a low speed.
[0020] It has the following beneficial effects:
[0021] (1) Anti-corrosion function: The coating relies on the dense network of PVA / OSA and HSEP-NH2 to build a cross-linked structure, forming a stable physical barrier to block the penetration of corrosive media. At the same time, ABT@HSEP-NH2 can release ABT slowly and form a passivation film on the metal surface. It works synergistically from both physical barrier and active protection aspects to greatly improve the long-term corrosion resistance of the coating.
[0022] (2) Self-healing function: There are dynamic Schiff base bonds inside the coating. When the coating is damaged by scratches, cracks or other damage, the chemical bonds can break and recombine autonomously to reconstruct the network structure. At the same time, the ABT released in the damaged area can form a protective film. Under the dual action, the coating defects can be restored to their original shape and protective ability, thus achieving efficient self-repair.
[0023] (3) Antibacterial function: ABT has antibacterial activity. After being released from ABT@HSEP-NH2, it can destroy the cell membrane structure of Escherichia coli and Staphylococcus aureus, and inhibit bacterial proliferation and biofilm formation. Attached Figure Description
[0024] Figure 1 This is a TEM image of ABT@HSEP-NH2 of the present invention;
[0025] Figure 2 The image shows the FT-IR spectrum of ABT@HSEP-NH2 from this invention.
[0026] Figure 3The N2 adsorption-desorption isotherm and pore size distribution diagram of ABT@HSEP-NH2 of this invention are shown below.
[0027] Figure 4 This is a release curve of ABT@HSEP-NH2 at different pH values according to the present invention;
[0028] Figure 5 The graph shows the change in low-frequency impedance of the complete PVA / OSA / 0.25ABT@HSEP-NH2 coating of this invention as a function of immersion time.
[0029] Figure 6 The graph shows the change in low-frequency impedance of the PVA / OSA / 0.25ABT@HSEP-NH2 coating with artificial scratches as a function of immersion time.
[0030] Figure 7 This is a statistical chart showing the antibacterial rate of the PVA / OSA / 0.25ABT@HSEP-NH2 hydrogel coating of the present invention against Escherichia coli and Staphylococcus aureus. Detailed Implementation
[0031] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] In one embodiment, a method for preparing ABT-loaded HSEP-NH2 nanocontainers is provided. The ABT@HSEP-NH2 is prepared using a vacuum loading method. Natural sepiolite initially presents as a tightly aggregated fiber bundle structure with numerous impurities adhering to its surface and pores, causing pore blockage. After stepwise purification and activation treatment involving hydrochloric acid washing, hydrogen peroxide oxidation, and secondary washing, the fiber bundles gradually untangle and disperse into loose, short, rod-shaped single fibers. Impurities are completely removed, the originally blocked pores are exposed, and a large number of hydroxyl groups on the surface are exposed, while the crystal framework remains intact. Subsequently, APTES is used for amination modification, and silane hydrolysis products are applied to the HSEP surface. Hydroxyl groups undergo dehydration condensation to form Si-O-Si covalent bonds, and amino functional groups are successfully grafted onto the fiber surface and pore walls, further improving fiber dispersion while maintaining a regular morphology. Finally, using a vacuum loading method, ABT is adsorbed onto the surface and pores of HSEP-NH2 through non-covalent interactions such as hydrogen bonding and van der Waals forces, ultimately preparing ABT@HSEP-NH2 nanocontainers. The product retains the original sepiolite fiber / short rod framework, with only a significant increase in surface roughness and a slight decrease in specific surface area and pore volume due to surface functionalization. Furthermore, the amino groups in ABT can provide additional cross-linking reaction sites for subsequent hydrogel formation, improving the stability of the hydrogel coating. The specific preparation steps include:
[0033] Step 1, Preparation of HSEP: Take 10 g of SEP, grind it and disperse it in 100 mL of deionized water, add hydrochloric acid to adjust the pH to 4, filter and dry at 60 °C. Take 4 g of dried SEP and add it to 40 mL of distilled water, stir at 60 °C for 30 min, add 30% hydrogen peroxide dropwise until no bubbles are generated, filter under vacuum and dry at 60 °C for 24 h. Take 2 g of the above product and add it to 20 mL of 1.0 mol / L hydrochloric acid, shake at 25 °C for 12 h, filter and wash until neutral, dry at 100 °C for 24 h and then crush and pass through a 200 mesh sieve to obtain acid-treated sepiolite, denoted as HSEP.
[0034] Step 2, Preparation of HSEP-NH2: 1 g APTES, 100 mL ethanol, and 10 mL deionized water were sonicated until the solution became clear and transparent to obtain a silane hydrolysate. Subsequently, 2 g HSEP was added to the silane hydrolysate and sonicated for 30 min. The mixture was then stirred at 80 °C for 12 h. After cooling, the mixture was collected by centrifugation and vacuum dried at 80 °C for 24 h to obtain HSEP-NH2.
[0035] Step 3, Preparation of ABT@HSEP-NH2: Using the vacuum loading method, HSEP-NH2 was added to a 0.1 mol / L ABT solution, stirred under vacuum for 30 min, stirred under normal pressure for 30 min, and the cycle was repeated 3 times. After centrifugation and drying, ABT@HSEP-NH2 was obtained.
[0036] In one embodiment, a PVA / OSA-based composite hydrogel smart coating with multiple protective functions and its preparation method are provided.
[0037] The coating offers multiple protective functions, including:
[0038] Corrosion protection: This coating relies on a dense PVA / OSA network and aminated sepiolite to construct a cross-linked structure, forming a stable physical barrier to prevent the penetration of corrosive media. At the same time, aminated sepiolite acts as a carrier to slowly release ABT, forming a protective film on the metal surface. This synergistic effect of physical barrier and active corrosion inhibition significantly improves the coating's long-term corrosion resistance.
[0039] Self-healing function: The coating contains dynamic Schiff base bonds. When the coating is damaged by scratches, cracks, or other defects, the chemical bonds can break and recombine autonomously, reconstructing the network structure. At the same time, the corrosion inhibitors released from the damaged area can help seal the defects. Under this dual action, the coating restores its shape and protective performance, achieving highly efficient self-repair.
[0040] Antibacterial function: ABT possesses excellent antibacterial activity. After slow release from the sepiolite carrier, it can disrupt the cell membrane structure of Escherichia coli and Staphylococcus aureus, inhibiting bacterial proliferation and biofilm formation. Coatings equipped with ABT can effectively resist the adhesion and corrosion of microorganisms in the marine environment.
[0041] The specific steps for preparing the smart coating include:
[0042] Preparation of S1 and OSA: 10 g of sodium alginate was dispersed in 50 mL of ethanol, and 50 mL of aqueous solution containing 8 g of sodium periodate was slowly added. The mixture was stirred at room temperature in the dark for 5 h. The reaction was terminated by adding 3 mL of ethylene glycol and stirring for 1 h. 150 mL of ethanol was added to precipitate the product. The product was filtered under vacuum and washed and purified three times to obtain a white powder. The obtained product was dissolved in deionized water and rotary evaporated at 60 °C for 4 h. After that, it was freeze-dried for 48 h to obtain OSA powder.
[0043] S2. Preparation of PVA / OSA hydrogel: Prepare 10 wt% PVA solution (95 °C, 2 h) and 3 wt% OSA solution (40 °C, 2 h), and mix PVA and OSA solution at a mass ratio of 1:1, which is denoted as PVA / OSA hydrogel;
[0044] S3. Preparation of composite hydrogel: Using PVA / OSA as the base hydrogel, 0.25% HSEP-NH2 was added as a crosslinking agent. After stirring evenly, PVA / OSA / 0.25HSEP-NH2 was obtained. In addition, 0.25wt% ABT@HSEP-NH2 was added to PVA / OSA. After thorough stirring, PVA / OSA / 0.25ABT@HSEP-NH2 hydrogel was obtained.
[0045] S4. First, clean the oxide layer, impurities, and adhering contaminants from the surface of the zinc sheet, and then dry it for later use. Allow the hydrogel obtained above to stand to remove bubbles, and then use a spin coating method to evenly apply the hydrogel to the pretreated zinc sheet surface (spin coat one layer at 2000 rpm, spin coat three layers at 500 rpm, each layer for 30 s). After coating, place the sample in a 30 °C oven to cure for 3 hours to obtain the corresponding hydrogel coating.
[0046] The following are specific examples:
[0047] Example 1, Preparation of HSEP: 10 g of SEP was ground and dispersed in 100 mL of deionized water. Hydrochloric acid was added dropwise to adjust the pH to 4. After filtration, the SEP was dried at 60 °C. 4 g of the dried SEP was added to 40 mL of distilled water and stirred at 60 °C for 30 min. 30% hydrogen peroxide was added dropwise until no bubbles were generated. After vacuum filtration, the SEP was dried at 60 °C for 24 h. 2 g of the above product was added to 20 mL of 1.0 mol / L hydrochloric acid and shaken at 25 °C for 12 h. The product was filtered and washed until neutral. After drying at 100 °C for 24 h, the product was pulverized and passed through a 200-mesh sieve to obtain HSEP.
[0048] Preparation of HSEP-NH2: 1 g APTES, 100 mL ethanol and 10 mL deionized water were sonicated until the solution was clear and transparent to obtain silane hydrolysate. Then, 2 g HSEP was added to the silane hydrolysate and sonicated for 30 min. The mixture was stirred at 80 °C for 12 h. After cooling, the mixture was collected by centrifugation and dried under vacuum at 80 °C for 24 h to obtain HSEP-NH2.
[0049] Preparation of ABT@HSEP-NH2: HSEP-NH2 was added to 0.1 mol / L ABT solution using a vacuum loading method. The mixture was stirred under vacuum for 30 min, then stirred under normal pressure for 30 min. This process was repeated three times. The mixture was then centrifuged and dried to obtain ABT@HSEP-NH2.
[0050] Example 2, Preparation of OSA: 10 g of sodium alginate was dispersed in 50 mL of ethanol, and 50 mL of aqueous solution containing 8 g of sodium periodate was slowly added. The mixture was stirred at room temperature in the dark for 5 h, and 3 mL of ethylene glycol was added and stirred for 1 h to terminate the reaction. Then, 150 mL of ethanol was added to precipitate the product. The product was filtered under vacuum and washed and purified three times to obtain a white powder. The obtained product was dissolved in deionized water and rotary evaporated at 60 °C for 4 h. After that, it was freeze-dried for 48 h to obtain OSA powder.
[0051] Preparation of PVA / OSA hydrogel: Prepare a 10 wt% PVA solution (95 °C, 2 h) and a 3 wt% OSA solution (40 °C, 2 h), and mix the PVA and OSA solutions at a 1:1 mass ratio to obtain the PVA / OSA hydrogel.
[0052] Example 3, Preparation of composite hydrogel: PVA / OSA as the base hydrogel, 0.25 wt% HSEP-NH2 was added as a crosslinking agent, and after stirring evenly, PVA / OSA / 0.25HSEP-NH2 was obtained.
[0053] In Example 4, 0.25 wt% of ABT@HSEP-NH2 was added to PVA / OSA, and after thorough stirring, PVA / OSA / 0.25ABT@HSEP-NH2 hydrogel was obtained.
[0054] Test Example 1, Figure 1 TEM electron microscopy observation of ABT@HSEP-NH2 yielded the following results: Figure 1 .
[0055] Results analysis:
[0056] Figure 1 In the process, the sample completely retained the inherent one-dimensional rod-shaped fiber skeleton structure of sepiolite, with intact fiber morphology and no obvious breakage or agglomeration. The results indicate that the amination and corrosion inhibitor loading process mainly affected the surface properties of sepiolite without changing its inherent fiber structure. It maintained excellent structural integrity throughout the modification process, providing a stable structural basis for the subsequent construction of a multifunctional hydrogel coating with self-healing, corrosion resistance and antibacterial functions.
[0057] Test Example 2, Figure 2 The FT-IR spectra of the PVA / OSA / 0.25ABT@HSEP-NH2 hydrogel are shown below. Figure 2 .
[0058] Results Analysis: In the PVA / OSA / 0.25ABT@HSEP-NH2 composite hydrogel, the aldehyde absorption peak at 1734 cm−1 corresponding to pure OSA completely disappeared, while Schiff base C=N double bond characteristic absorption peaks appeared at 1520 cm−1 and 1630 cm−1. This proves that the aldehyde group of OSA can undergo Schiff base reactions with the amino groups on the surface of ABT@HSEP-NH2 and in the amino group of ABT molecule, respectively, to construct a dynamic cross-linked network. In addition, the hydrogen bond absorption band of PVA / OSA, the sepiolite framework peak, and the characteristic peak of ABT are retained at the same time, indicating that the components are well compatible. This multi-cross-linked structure is the reason why the composite hydrogel has excellent structural stability, self-healing, anti-corrosion, and antibacterial properties.
[0059] Test Example 3, Figure 3 The N2 adsorption-desorption isotherms and pore size distribution diagram of ABT@HSEP-NH2 are shown.
[0060] Results Analysis: The N2 adsorption-desorption and pore size distribution curves of ABT@HSEP-NH2 exhibit typical Type IV isotherms for mesoporous materials. Its specific surface area is 195 m² / g, and its pore volume is 0.64 cm³ / g, which are smaller than those of HSEP-NH2 (256 m² / g and 0.82 cm³ / g), indicating that ABT occupies part of the channels and surface sites of HSEP-NH2. This proves that ABT has been successfully loaded into HSEP-NH2.
[0061] Test Example 4, Figure 4 Release curves of ABT@HSEP-NH2 at different pH values.
[0062] Results analysis: Under different pH conditions, ABT exhibited a rapid release in the early stage followed by a gradual release. The cumulative release was relatively high under neutral conditions (0.53 mmol / L), while the release was slightly lower under acidic and alkaline conditions (0.48 mmol / L), indicating that ABT@HSEP-NH2 exhibits certain environmentally sensitive release behavior. This slow-release characteristic is beneficial for the coating to continuously release corrosion inhibitors in near-neutral corrosive environments such as seawater, thereby exerting active anti-corrosion and antibacterial effects.
[0063] Test Example 5, Figure 5 The change in low-frequency impedance (|Z|0.01Hz) of a complete PVA / OSA / 0.25ABT@HSEP-NH2 coating with immersion time.
[0064] Results analysis: Figure 5The low-frequency impedance curve of the complete PVA / OSA / 0.25ABT@HSEP-NH2 hydrogel coating in 3.5 wt% NaCl solution is shown. The impedance modulus reaches 2.45×104 Ω・cm2 on the first day of immersion. Although the impedance modulus decreases after 30 days of immersion, it is still higher than that of the pure PVA / OSA coating (2.04×103 Ω・cm2). Under external conditions, ABT is slowly released and forms a passivation protective film on the metal surface, achieving active corrosion protection. The dynamic Schiff base bonds in the complete coating network stabilize the coating structure, and the physical barrier and corrosion inhibition and slow release work together to give the coating long-term corrosion resistance.
[0065] Test Example 6, Figure 6 The low-frequency impedance of a PVA / OSA / 0.25ABT@HSEP-NH2 coating with artificial scratches varies with immersion time.
[0066] Results Analysis: Artificial scratching simulated mechanical damage to the coating caused a sharp decline in its protective function; however, after only 4 hours of immersion, the coating's electrochemical impedance recovered from 5.37 × 10² Ω·cm² to 1.51 × 10⁴ Ω·cm², demonstrating that ABT@HSEP-NH₂ possesses highly efficient self-healing properties. On one hand, the amino groups in HSEP-NH₂ and both OSA and ABT molecules can form dynamic Schiff base bonds with the OSA aldehyde groups, and numerous reversible cross-linking sites drive rapid reconstruction of the fractured network. On the other hand, ABT molecules released from the damaged area can form a protective film on the metal surface, inhibiting localized corrosion in situ. The synergistic effect of these two factors allows the coating to restore its corrosion resistance while repairing its structure.
[0067] Test Example 7, Figure 7 A statistical chart showing the antibacterial rate of PVA / OSA / 0.25ABT@HSEP-NH2 hydrogel coating against Escherichia coli and Staphylococcus aureus.
[0068] Results Analysis: Based on the plate colony counts of *Escherichia coli* and *Staphylococcus aureus* on the coating surface, the coating showed inhibition rates of 99.02% and 97.04% against *E. coli* and *S. aureus*, respectively. The inhibition rates for both strains were extremely high, demonstrating the coating's highly effective antibacterial capabilities. Its superior antibacterial performance stems from the slow-release ABT active species in the system. ABT can act on bacterial cell membranes, disrupting membrane integrity and significantly inhibiting bacterial adhesion and reproduction. This effectively mitigates biofilm formation on metal surfaces in marine environments, reduces the risk of microbial-induced corrosion, and achieves a synergistic effect of corrosion prevention and antibacterial function.
[0069] Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art and related fields based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention. Structures, devices, and operating methods not specifically described and explained in the present invention, unless otherwise specified or limited, shall be implemented according to conventional means in the art.
Claims
1. A self-healing antibacterial and antiseptic hydrogel coating of aminated sepiolite loaded with 2-aminobenzothiazole, characterized in that, Includes a PVA / OSA matrix and uniformly dispersed ABT@HSEP-NH2 nanocontainers; The ABT@HSEP-NH2 nanocontainer uses APTES-grafted HSEP as a carrier and loads ABT using a vacuum-atmospheric pressure cycling method with an addition amount of 0.25 wt%. The aldehyde groups in the OSA can undergo Schiff base reactions with the amino groups on the HSEP-NH2 and ABT, respectively, to form a covalent cross-linked network with both dynamic self-healing properties and antibacterial and antiseptic functions.
2. The self-healing antibacterial and antiseptic hydrogel coating of aminated sepiolite supported on 2-aminobenzothiazole according to claim 1, characterized in that, The PVA and OSA are compounded at a mass ratio of 1:1 to form a coating matrix hydrogel.
3. The self-healing antibacterial and antiseptic hydrogel coating of aminated sepiolite supported on 2-aminobenzothiazole according to claim 1, characterized in that, The preparation method of ABT@HSEP-NH2 includes the following steps: Step 1: SEP is sequentially subjected to acid etching, oxidation to remove impurities, and secondary acid purification to obtain purified sepiolite HSEP; Step 2: React the HSEP with APTES hydrolysate to obtain aminated sepiolite HSEP-NH2; Step 3: Add HSEP-NH2 to the ABT solution, and stir under vacuum and atmospheric pressure as one cycle. Repeat the cycle to promote ABT loading. Then centrifuge and dry to obtain ABT@HSEP-NH2 nanocontainers.
4. The self-healing antibacterial and antiseptic hydrogel coating of aminated sepiolite supported on 2-aminobenzothiazole according to claim 1, characterized in that, The covalent cross-linked network endows the coating with self-healing properties, and the ABT can be slowly released under external triggering to form a protective film on the metal surface.
5. The method for preparing the coating according to any one of claims 1-4, characterized in that, Includes the following steps: S1. Preparation of OSA: Sodium alginate was dispersed in an ethanol system and oxidized with sodium periodate under light-protected conditions. The reaction was terminated with ethylene glycol. After purification by ethanol precipitation and freeze-drying, oxidized sodium alginate OSA was obtained. S2. Prepare PVA solution and OSA solution separately, and mix them at a mass ratio of 1:1 to obtain hydrogel coating solution; S3. Add 0.25 wt% ABT@HSEP-NH2 to the hydrogel solution, stir and mix thoroughly, and let stand to remove bubbles to obtain the composite hydrogel PVA / OSA / 0.25ABT@HSEP-NH2; S4. After grinding, ultrasonically cleaning with ethanol and drying the zinc sheet substrate, the composite hydrogel solution is applied to the zinc sheet surface using a spin coating process and dried in an oven to obtain the self-healing antibacterial and anti-corrosion hydrogel coating.
6. The preparation method according to claim 5, characterized in that, The spin coating process includes: first, forming a base layer by spin coating at a high speed, and then continuously spin coating three layers at a low speed.
7. The application of the coating according to any one of claims 1-4 in the protection of metal components in a marine high-salt corrosion environment.
8. The application according to claim 7, characterized in that, The metal components include ship structural parts, offshore wind power equipment, marine oil and gas extraction equipment, and other metal parts that have been in long-term service in the corrosive marine environment.
